Encouraging achievement in external grant performance - Asdarina, Yahya (Penerbit UMP, 2013)
Universiti Malaysia Pahang (UMP) researchers recorded on encouraging achievement in external grant performance for research works between July and December 2013. The passion and commitment shown by them in pursuing research excellence was reflected in the success of them acquiring 81 external research project involving a sum of RM 7,547,284.22.